PERSEPSI NASABAH TERHADAP PENERAPAN AKAD MUDHARABAH DI BMT MITRA MADANI SYARIAH BRAJA SELEBAH LAMPUNG TIMUR - Dewi Trismahwati; MOH. ABDUR ROHMAN WAHID; NUR INDAH SARI (STAI Darussalam Lampung, 2023)
Mudarabah has been one of the most popular goods among BMT Mitra Madani Syariah's customers. Mudharabah is expected to account for more than 60% of contracts in 2020. Meanwhile, BMT Mitra Madani Syariah has implemented mudharabah principles in accordance with Islamic law in its application. The goal of this study was to establish consumer perceptions of mudharabah implementation in BMT Mitra Madani Syariah, as well as the elements that influence it, based on the above description. This is a qualitative descriptive research project. Purposive sampling is a strategy for determining the participants. Five people are the focus of the research. According to the findings, the individuals had a positive opinion of mudarabah. acceptance does not come without justification. One of the causes is replaces bank interest with a sharing system. Another argument is that the rate system is seen as an unjust system for determining profit (revenue) that is particular to money lent, whereas company has the potential for profit or loss. Mudharabah, on the other hand, was seen as more fair since mudharabah paid attention to the possibility. Several things influence the perception that develops. Internal elements, which include psychological requirements, history, and experience, are the first. Psychological demands, such as mudhrabah contracts, are easier to fulfill and make it easier to continue the business. Other consumers' reported happiness with the mudharabah system is explained by stimulation. Keyword: Mudharabah System, Perception